On decay constants and orbital distance to the Sun—part II: beta minus decay. (28th November 2016) - Pommé, S; Stroh, H; Paepen, J; Van Ammel, R; Marouli, M; Altzitzoglou, T; Hult, M; Kossert, K; Nähle, O; Schrader, H; Juget, F; Bailat, C; et al.
Abstract: Claims that proximity to the Sun causes variations of decay constants at the permille level have been investigated for beta-minus decaying nuclides. Repeated activity measurements of 3 H, 14 C, 60 Co, 85 Kr, 90 Sr, 124 Sb, 134 Cs, 137 Cs, and 154 Eu sources were performed over periods of 259 d up to 5 decades at various nuclear metrology institutes. Residuals from the exponential decay curves were inspected for annual oscillations. Systematic deviations from a purely exponential decay curve differ in amplitude and phase from one data set to another and appear attributable to instabilities in the instrumentation and measurement conditions. Oscillations in phase with Earth's orbital distance to the Sun could not be observed within 10 −4 –10 −5 range precision. The most stable activity measurements of β − decaying sources set an upper limit of 0.003%–0.007% to the amplitude of annual oscillations in the decay rate. There are no apparent indications for systematic oscillations at a level of weeks or months.